2019
DOI: 10.3390/molecules24173195
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Constituents and Biological Activity Profiles on Pleione (Orchidaceae)

Abstract: Pleione (Orchidaceae) is not only famous for the ornamental value in Europe because of its special color, but also endemic in Southern Asia for its use in traditional medicine. A great deal of research about its secondary metabolites and biological activities has been done on only three of 30 species of Pleione. Up to now, 183 chemical compounds, such as phenanthrenes, bibenzyls, glucosyloxybenzyl succinate derivatives, flavonoids, lignans, terpenoids, etc., have been obtained from Pleione. These compounds hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 47 publications
(49 reference statements)
1
15
0
Order By: Relevance
“…The chemical difference reflected by HPLC fingerprints can only be a result of genetic difference of these studied species. Various chemical compounds, such as phenanthrenes, bibenzyls, glucosyloxybenzyl succinate derivatives and flavonoids, have been found in pseudobulbs of previous studied Pleione species [9] . Dactylorhin A and militarine characterized in our study were demonstrated to have the effects of neuroprotection and cognitive impairment [21–23] .…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…The chemical difference reflected by HPLC fingerprints can only be a result of genetic difference of these studied species. Various chemical compounds, such as phenanthrenes, bibenzyls, glucosyloxybenzyl succinate derivatives and flavonoids, have been found in pseudobulbs of previous studied Pleione species [9] . Dactylorhin A and militarine characterized in our study were demonstrated to have the effects of neuroprotection and cognitive impairment [21–23] .…”
Section: Discussionsupporting
confidence: 49%
“…Various chemical compounds, such as phenanthrenes, bibenzyls, glucosyloxybenzyl succinate derivatives and flavonoids, have been found in pseudobulbs of previous studied Pleione species. [9] Dactylorhin A and militarine characterized in our study were demonstrated to have the effects of neuroprotection and cognitive impairment. [21 -23] The determination of these two compounds therefore can be used for the quality control of P. bulbocodioides and P. yunnanensis.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Plants, such as the Lauraceae family, especially the genera of Machilus, Ocotea, and Nectandra are rich sources of lignans. Additionally, Annonaceae, Orchidaceae, Berberidaceae, and Schisandraceae family contain a large number of constituents of lignans and neolignans [3][4][5]. Up to date, lignans are found in over 70 families in plant kingdom, and more than 200 classical lignans and 100 neolignans have been characterized [6].…”
Section: Introductionmentioning
confidence: 99%
“…Plants from the orchid family have been widely used in the traditional Chinese medicine (TCM) and oriental folk medicines to treat tumors, burns, frostbite, coughs, tuberculosis, bronchitis and gastrointestinal bleeding, as well as to remove “heat and toxin” [ 1 ]. According to previous reports, extracts from a variety of different terrestrial orchids contain remarkable amounts of stilbenes and dihydrostilbenes, such as dihydro-resveratrol ( 3 ), moscatilin ( 4 ), resveratrol ( 5 ) and combretastatin A-4 ( 6 ) [ 2 , 3 , 4 , 5 , 6 , 7 , 8 ], which are known to exhibit antineoplastic, antimitotic and anticarcinogenic properties as well as inhibit oxidative stress ( Figure 1 ) [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. The structurally unprecedented dihydrostilbenes shancigusin C ( 1 ) and bletistrin G ( 2 ), both featuring 4-hydroxybenzyl substituents, were isolated from the orchidaceous species Pleione yunnanensis and Bletilla striata in 2009 and 2019, respectively [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%